Plan estratégico del nuevo centro de capacitación talento humano, que impulse el desarrollo y bienestar social del recinto la Virginia del sector rural del cantón Quevedo. Año 2012 - Rodríguez Sánchez, Sandra Patricia (2014)
Virginia The sector is located at Km 5 ½ via Junction 45 minutes from the city in the rural area of Quevedo Canton. It is one of the communities that suffer many calamities, such as utilities, asphalt, insecurity, lack of transportation, among others. This causes this sector remains the exception of both economic and social development and not power or even the basic needs which prevents good living within Ecuador. With the social and economic diagnosis to be performed at the Virginia industry could identify strengths and weaknesses. Getting the results of SWOT analysis could be performed allowing the strategic plan analyzing the external and internal causes to implement a training plan in the Quevedo Canton Virginia sector. Raised all strategies in the strategic plan can pursue an economic activity in the sector by promoting and strengthening community organizations for the production and generation of surplus market and increased household incomes. The Campus Virginia is a highly productive sector and has land in order to perform economic activities and construction of recreational places, have projects that are stalled because they do not give you the right process , which is why the proposals presented are the proper execution of projects to complete , as the request and creation of other works that benefit is to the community at large in both the economic and social field . Improvingthequality of life